(untitled) (Global Journal of Human-Social Science, 2014)
Inour paper we present one part of the results of our research which focused on factors that determine young people’s attitudes towards the older generation and the level of their social and inter-generational solidarity. In our article we evaluate the conditions and possibilities of how to reach social peace taking into account young people’s attitudes and values and we analyze established difference in social attitudes between young people from rural areas and those from towns or cities (represented here by respondents from Prague). Moreover, we present our conclusions: are there any threats (and which ones) to social peace and through it to social and regional development which could be triggered by how young people perceive the justification of social policy and its principles’ content.